A Systemic Lupus Erythematosus Patient With Febrile Neutropenia Developing After Intraocular Administration of Bevacizumab - Hamdi SÖZEN; Gönen MENGİ and Bülent HÜDDAM and Selmin ÇAYLAK and Mehmet DEVEER and Volkan KARAKUŞ and Burak Ekrem ÇİTİL (Archives of Rheumatology, 2016)
In this article, we report a case with febrile neutropenia occurring after implementation of intraocular bevacizumab. A 60-year-old female patient who had received intravitreal bevacizumab applied to hospital for oral lesions accompanying fever and neutropenia. In spite of empiric antibiotherapy, patient’s clinical condition did not improve. Her sputum culture yielded Stenotrophomonas maltophilia. Trimethoprim/ sulfamethoxazole and levofloxacin were commenced according to antibiogram. In immunologic evaluation, antinuclear antibodies and anti-double stranded deoxyribonucleic acid were positive as compatible with systemic lupus erythematosus. After proper antibiotic treatment, patient’s clinical symptoms resolved. Development of severe neutropenia after procedures which are not expected to create systemic adverse effects should bring to mind underlying immunosuppressive diseases such as systemic lupus erythematosus.